2021
DOI: 10.52547/rbmb.10.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Expression of Some Oncogenes and Predisposing Behaviors Contributing to the Aggressiveness of Prostate Cancer

Abstract: Background: Prostate cancer is the second most common cancer in men in Iran. It can be treated in the early stages of the disease; therefore, early diagnosis can be lifesaving. The aim of this study was to investigate the molecular expression of some oncogenes and predisposing behaviors contributing to the aggressiveness of prostate cancer. Methods: In this case-control study, prostate cancer specimens were collected from both patients and healthy volunteers. Several factors such as age, family history, smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Moreover, FGF14 and SNX10 have demonstrated tumor suppressive properties in colorectal cancer [ 43 , 44 ]. Conversely, decreased expression of GLB1L2 and TRAK2 has been documented in prostate cancer and osteosarcoma, respectively [ 23 , 45 ]. Hence, these proteins have the potential to serve as good prognostic biomarkers for FMC, especially NmFMC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FGF14 and SNX10 have demonstrated tumor suppressive properties in colorectal cancer [ 43 , 44 ]. Conversely, decreased expression of GLB1L2 and TRAK2 has been documented in prostate cancer and osteosarcoma, respectively [ 23 , 45 ]. Hence, these proteins have the potential to serve as good prognostic biomarkers for FMC, especially NmFMC.…”
Section: Discussionmentioning
confidence: 99%
“…Glb1l2 is a member of galactosidase, and its physiological function is largely unknown. A reduction 46 in GLB1L2 expression can lead to a decrease in the expression of a tumor-suppressor protein called Inter-Alpha-Trypsin Inhibitor Heavy Chain Family Member 5, which is associated with malignant progression and unfavorable prognosis, indicating a tumor-suppressor function in breast, colon, bladder, hepatic cancers, and lung adenocarcinoma, etc. Jhun et al 47 reported a reduced GLB1L2 expression in patients with prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Patients included in this study were treated prior to 2013, and PSMA-PET was not available during diagnosis (CT or MRI and bone scan only). Our results highlight the importance of implementing advanced imaging techniques, we are currently evaluating the role of oxygenenhanced MRI (OE-MRI) (52) or Restriction Spectrum Imaging (RSI) (53) in predicting the extent of microscopic disease spread.…”
Section: Gy Inmentioning
confidence: 98%